2012
DOI: 10.1016/j.yhbeh.2012.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Sex effects on neurodevelopmental outcomes of innate immune activation during prenatal and neonatal life

Abstract: Humans are exposed to potentially harmful agents (bacteria, viruses, toxins) throughout our lifespan; the consequences of such exposure can alter central nervous system development. Exposure to immunogens during pregnancy increases the risk of developing neurological disorders such as schizophrenia and autism. Further, sex hormones, such as estrogen, have strong modulatory effects on immune function and have also been implicated in the development of neuropathologies (e.g., schizophrenia and depression). Simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 139 publications
(208 reference statements)
4
36
1
Order By: Relevance
“…These discrepancies could be attributable to the different periods of neonatal LPS exposure and different doses used for the LPS challenge. The type of immunogen (e.g., LPS, polyriboinosinic-polyribocytidylic acid, and cytokines), dose, and time of administration (e.g., early vs. late gestation, neonatal period) may interact with sex and play significant roles in the observed variability (Rana, Aavani, & Pittman, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies could be attributable to the different periods of neonatal LPS exposure and different doses used for the LPS challenge. The type of immunogen (e.g., LPS, polyriboinosinic-polyribocytidylic acid, and cytokines), dose, and time of administration (e.g., early vs. late gestation, neonatal period) may interact with sex and play significant roles in the observed variability (Rana, Aavani, & Pittman, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Additional experiments revealed that PPI abnormalities were lowest during estrus in female rats. This is mirrored in women; symptoms of schizophrenia are most severe when estrogen is low [22]. These findings indicate that there is an interaction between sex, the CNS, and the immune system, that results in different outcomes of schizophrenia.…”
Section: Sex Differencesmentioning
confidence: 84%
“…Different areas of the brain develop at different times; therefore immune dysfunction can have varied developmental outcomes depending on what stage in development infection occurs [21]. Furthermore, considering that cytokines have different, even opposite effects depending on developmental stage, outcomes can vary immensely based on time [22].…”
Section: Animal Models Of Schizophreniamentioning
confidence: 99%
“…Male zebra finches challenged with the endotoxin lipopolysaccharide (LPS) early in life exhibited reduced performance on a novel foraging task when tested approximately one year later, whereas female performance was not impacted by this endotoxin challenge [10]. As with the effects of immune challenge on neophobia, this demonstrates that immune activation may have sex-specific effects on behavior and future research should explicitly test for sex differences [25]. …”
Section: Adult Behaviors Programmed By Early Life Immune Activationmentioning
confidence: 99%